Islamic Parenting as an Effort to Educate the Islamic Character of Alpha Generation - Ramadhanul Ikhsan; Cisia Padila; Tegu Reski Amanah; Pela Safni; Muhammad Kosim (al-Afkar, Journal For Islamic Studies, 2025)
The development of the times brings various changes to every human being from various sides. The alpha generation is a generation full of challenges. The alpha generation needs to receive guidance, especially from parents, to develop good character and be able to avoid bad things. The aim of this research is to find out how to educate alpha generation children so that Islamic character is formed through Islamic parenting. This research is a type of qualitative research with a library research approach. The technique used in collecting data is documentation. Data sources are obtained from sharing sources such as books, journals, articles and other data. The data analysis used is content analysis and descriptive narrative. This research shows that educating alpha generation children for parents is a big challenge in this era. Islamic parenting itself views that the parenting process starts from choosing a partner. Parents must be able to educate their children, especially regarding the use of technological media. Parents are central figures in educating children. It is absolutely necessary for parents to understand their children's world, especially with regard to the digital world. Parents can use Islamic parenting to educate the alpha generation so that they have a stronghold and avoid things that are prohibited. Based on the results of this research, educating Islamic character through Islamic parenting must start early and must be adapted to the child's development stage